Background paper for developing a policy for the use of rabies biologicals and vaccination of humans in India - Mysore Kalappa Sudarshan; Doddabele Hanumanthaiah Ashwath Narayana (Wolters Kluwer Medknow Publications, 2019)
National Rabies Control Programme, India, is in operation since 2012-2013 without much impact due to poor funding and no set policy for the rabies prevention and control. An effort was made to develop a draft policy paper which can help the Government of India to develop a national rabies vaccination policy for humans and for achieving the goal of zero dog-mediated human rabies deaths by the year 2030. A technical stakeholders meeting was held under the chairmanship of the Drug Controller General of India at New Delhi in December 2017 to discuss the problems and solutions for providing essential rabies postexposure prophylaxis (PEP). The following problems and dilemmas were identified: frequent shortages of life-saving rabies vaccines and rabies immunoglobulin for PEP; as rabies vaccines are mostly procured by the state governments that often face resource crunch and hurdles in logistics within the states; production levels of rabies biologicals in the public sector are low; and the export of rabies biologicals from the private sector needs to be critically evaluated in the context of frequent stock-outs in the domestic market and also the national vaccine security.